Colonial administration and land reform in East Asia
1 online resource (xi, 206 pages)
Keywords: "This book argues that as colonialism brought the concept of individual, as opposed to collective, land ownership to indigenous society, along with Western surveying techniques, the changes that resulted altered the relationship of the state to its citizens, and, thereby, the structure of local societies. The book considers these issues in all of East Asia, including China, Japan and Korea, focusing in particular on Hong Kong, which was subject to British rule from 1842 to 1997, and on Taiwan, which was subject to Japanese rule from 1895 to 1945. The book discusses how, although the main impact of land ownership by individuals and modern surveying were felt after colonialism had ended, it is by studying the introduction of these factors that their impact can be most clearly understood."--Provided by publisher.